Implementation of Transformational Leadership on the Performance of PAUD Teachers in the Digital Era - Alam, Syamsir; Badeni, Badeni; Kristiawan, Muhammad; Yanti, Fitri April (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research aimed to investigate the impact of the implementation of transformational leadership on the performance of Early Childhood Education (PAUD) teachers in the digital era. The importance of the research topic lies in its potential to improve the quality of early childhood education, enhance teacher performance, and provide valuable insights into effective leadership practices in the digital era. The research method employed was a survey, with data collected through questionnaires distributed to 100 PAUD teachers and 20 PAUD principals experienced in using digital technology in teaching. The collected data were analyzed using descriptive and regression statistical techniques. The research results indicate that transformational leadership significantly enhances the performance of PAUD teachers in integrating digital technology into their teaching practices. Innovation encouragement, creativity development, and sustained support from school leaders are vital in implementing this leadership approach. This research concludes that transformational leadership plays a vital role in improving the quality of PAUD learning in the digital era. Therefore, PAUD school leaders need to actively promote this leadership approach to support teachers in addressing the challenges of digital technology.